Biological characteristics and whole‐genome analysis of the potential probiotic, Lactobacillus reuteri S5. (30th January 2022) - Shi, Shuiqin; Dong, J.; Cheng, X.; Hu, J.; Liu, Y.; He, G.; Zhang, J.; Yu, H.; Jia, L.; Zhou, D.
Abstract: Lactic acid bacteria are micro‐organisms used for probiotic purposes and form major parts of human and mammalian intestinal microbiota, exerting important health‐promoting effects on the host. Here, we evaluated Lactobacillus reuteri strain S5 isolated from the intestines of healthy white feather broilers. Lactobacillus reuteri S5 grew best after 20 h of incubation in MRS medium. Lactic acid production was 1·42 mmol l −1 at 24 h, which was well tolerated. Activities of T‐AOC, GSH‐Px and T‐SOD in the cell‐free fermentation supernatant of L. reuteri S5 were higher than those in the bacteria, and the strain showed good hydrophobicity in vitro . The dominant carbon and nitrogen sources of L. reuteri S5 were glucose and soybean meal. A high‐quality complete genome map of L. reuteri S5 was obtained using a Pacbio nanopore third‐generation sequencing platform. The results showed that L. reuteri S5 possesses a complete primary metabolic pathway, encoding the main functional enzymes of the glycolysis pathway and pentose phosphate pathway. The genome contains genes encoding antioxidants and conferring tolerance to inorganic salt ions, acids and bile salts. This study shows that L. reuteri S5 is a probiotic strain with excellent probiotic characteristics and has great potential for the development of feed additives to promote animal health. Abstract : Significance and Impact of the Study: Lactobacillus reuteri is the most common intestinal micro‐organism, colonizing almost all vertebrate intestines. Strain specificity of lactobacillus makes it necessary to analyse and evaluate the strain information and function of potential probiotic strains such as L. reuteri S5. The whole genome of L. reuteri strain S5 was analysed using whole‐genome sequencing and bioinformatics. This work shows that L. reuteri S5 is a probiotic strain with excellent probiotic characteristics and has great potential for developing animal feed additives to promote health.